Ich bin dein Mensch = I'm your man [videorecording (Blu-Ray)] - Schrader, Maria, 1965-; Schomburg, Jan, 1976-; Stevens, Dan, 1982-; Eggert, Maren; Hüller, Sandra; Löw, Hans, 1976-; Braslavsky, Emma, 1971- (Decal, 2021)
In order to obtain funds for her research, Alma is persuaded to participate in an extraordinary study. For three weeks she is required to live with Tom, a humanoid robot designed to be the perfect life partner for her, trailored to her character and needs.